2021
DOI: 10.3390/atmos12121592
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variation of Volatile Organic Compounds in Ambient Air of Almaty City, Kazakhstan

Abstract: Air pollution is one of the primary sources of risk to human health in the world. In this study, seasonal and spatial variations of multiple volatile organic compounds (VOCs) were measured at six sampling sites in Almaty, Kazakhstan. The seasonal and spatial variations of 19 VOCs were evaluated in 2020, including the periods before and after COVID-19 lockdown. The concentrations of 9 out of 19 VOCs had been changed significantly (p < 0.01) during 2020. The maximum concentrations of total VOCs (TVOCs) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The highest value of BTEX was observed at Amritsar, while the lowest was in Khanna. The high level at Amritsar during the lockdown may be because of the stubble or biomass burning cases, rubber and pharmaceutical industries, and limited transportation activities of essential duty and supply vehicles (Truc & Oanh, 2007;Ibragimova et al, 2021;Rathod et al, 2021;Sahu et al, 2022).…”
Section: Identi Cation Of Voc Characteristic Pollutants During the Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…The highest value of BTEX was observed at Amritsar, while the lowest was in Khanna. The high level at Amritsar during the lockdown may be because of the stubble or biomass burning cases, rubber and pharmaceutical industries, and limited transportation activities of essential duty and supply vehicles (Truc & Oanh, 2007;Ibragimova et al, 2021;Rathod et al, 2021;Sahu et al, 2022).…”
Section: Identi Cation Of Voc Characteristic Pollutants During the Pa...mentioning
confidence: 99%
“…A less than 1 T/B ratio shows non-tra c sources such as coal burning, biomass, and bio-fuel, while the value of T/B ratio is more than 1, it indicates the major contribution of tra c-related sources. When vehicle emissions act as a major BTEX source which is commonly seen, the T/B ratio was reported low (Ibragimova et al, 2021). Before the pandemic, the toluene and benzene (T/B) ratio was calculated for the different monitoring stations and were observed, 0.57 µg/m 3 for Amritsar, 1.38 µg/m 3 for Ludhiana and 2.97 µg/m 3 for Patiala, which indicates non-tra c related sources such as biomass, coal burning and biofuel in Amritsar and Ludhiana (Ibragimova et al 2021).…”
Section: Source Identi Cation Of Btexmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kazakhstan, the impact of COVID-19 restriction measures on air quality was studied in two cities: Almaty (Kerimray et al 2020b ; Ibragimova et al 2021 ) and Ust-Kamenogorsk (Assanov et al 2021b ). Assanov et al ( 2021b ) reported that the concentration of Total Suspended Particles (TSP) increased by 13–21%, while SO 2 and NO 2 levels did not change significantly in Ust-Kamenogorsk (Kazakhstan) during the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…In Almaty (Kazakhstan), concentrations of CO, NO 2, and PM 2.5 decreased by 49, 35 and 21%, respectively, with an insignificant increase of SO 2 (Kerimray et al 2020b ). The changes of volatile organic compound concentrations during the lockdown in Almaty showed an increase in the levels of benzene and toluene by 2–3 times (Kerimray et al 2020b ) and in the levels of ethylbenzene and benzaldehyde by 2–5 times (Ibragimova et al 2021 ). Thus, air pollution could be substantially improved during the lockdown in the cities where transport was a major source.…”
Section: Introductionmentioning
confidence: 99%